2016
DOI: 10.1186/s12872-016-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

Young smoker “ABCD” vascular assessment: a four-step ultrasound examination for detecting peripheral, extra and intra-cranial early arterial damage

Abstract: BackgroundCigarette smoking is known as a major risk factor in the pathogenic mechanisms of stroke, coronary and peripheral artery disease (CAD and PAD), even in young subjects. The aim of this study is the creation of a four-step ultrasound examination to evaluate and monitor the peripheral, the extra and the intra-cranial assessment of the arterial early damage in smokers. The evaluations of A, the Ankle-brachial index, ABI, B, the Breath holding index, BHI, C, the Carotid intima media thickness, CIMT, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The values of Δ Y r for smokers were significantly ( p = 0.04) lower than those of non-smokers ( Figure 4 ), demonstrating a degeneration of the arteriolar vasomotor function due to chronic smoking in young smokers, even after a few years of smoking. This result agrees with those of previous studies based on BHI and visually evoked CBF response; the BHI [ 25 ] and visually evoked CBF [ 19 , 26 ] decreased in young smokers when compared with non-smokers. Δ Y r obtained from our spectral analysis of the MR time series signals of cerebral venous blood reflects the arteriolar vasomotor function, and its degeneration due to chronic smoking in young smokers was successfully demonstrated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The values of Δ Y r for smokers were significantly ( p = 0.04) lower than those of non-smokers ( Figure 4 ), demonstrating a degeneration of the arteriolar vasomotor function due to chronic smoking in young smokers, even after a few years of smoking. This result agrees with those of previous studies based on BHI and visually evoked CBF response; the BHI [ 25 ] and visually evoked CBF [ 19 , 26 ] decreased in young smokers when compared with non-smokers. Δ Y r obtained from our spectral analysis of the MR time series signals of cerebral venous blood reflects the arteriolar vasomotor function, and its degeneration due to chronic smoking in young smokers was successfully demonstrated.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that CBF decreased gradually at age from 20s to 90s and CBF in smokers was significantly lower than that in non-smokers at all ages [ 23 ]. Even in the late young-age smokers (around 30 years old), CBF [ 24 ], BHI [ 25 ], and visually evoked CBF response [ 19 , 26 ] were lower than those in non-smokers, showing a degeneration of arteriolar vasomotor function due to chronic smoking of approximately 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, THE or other elastographic techniques might provide interesting additional information on the role of smoking- and non-smoking-related vascular pathology such as rupture in the formation of aortic aneurysms. In our volunteers, THE detected stiffness changes of the aortic wall in smokers, although the aortic diameter, currently used for assessment of vascular health, showed no significant differences between the two groups 15 , 16 . THE has the potential advantage of providing both morphological and biomechanical information in a single examination.…”
Section: Discussionmentioning
confidence: 56%
“…A 4-step non-invasive ultrasound assessment protocol, ABCD may be useful for detection and monitoring of early arterial damage in smokers (A, the Ankle-Brachial Index (ABI); B, the Breath Holding Index (BHI); C, the Carotid Intima Media Thickness (CIMT); and D, the Diameter of the abdominal aorta). 22 Following the failure of advice, encouragement and motivational interventions or in addition to them NRT varenicline or bupropion should be offered to assist cessation. Electronic cigarettes deliver the addictive nicotine without the vast majority of tobacco chemicals and are probably less harmful than tobacco.…”
Section: Effect Of Smoking On Therapymentioning
confidence: 99%